2021
DOI: 10.1039/d1na00514f
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis and electrocatalytic applications of atomically precise gold nanoclusters

Abstract: Nanoclusters are composed of metal atoms and ligands with sizes up to 2-3 nm. Due to their stability and unique structure, gold nanoclusters with precise atomic numbers have been widely...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 119 publications
(215 reference statements)
0
19
0
Order By: Relevance
“…33 They first synthesized and analyzed Au 25 (PET) 18 , confirming the purity of NCs. Subsequently, the Au 25 (PET) 18 NCs were successfully loaded on sulfur-doped graphene via a facilitated mixing method. Compared to those loading on bare graphene, Au 25 @S-G was no observed trend of aggregation, which was attributed to the bond between sulfur and the Au atom.…”
Section: Electrochemical Synthesis Of Ammoniamentioning
confidence: 95%
“…33 They first synthesized and analyzed Au 25 (PET) 18 , confirming the purity of NCs. Subsequently, the Au 25 (PET) 18 NCs were successfully loaded on sulfur-doped graphene via a facilitated mixing method. Compared to those loading on bare graphene, Au 25 @S-G was no observed trend of aggregation, which was attributed to the bond between sulfur and the Au atom.…”
Section: Electrochemical Synthesis Of Ammoniamentioning
confidence: 95%
“…The success in synthesizing a series of Au n (SR) m NCs with different sizes provides an excellent chance to explore the size-dependent catalytic activity at an unprecedented atomic level. [44][45]53,54] As shown in Figure 1, Jin and co-workers classified the Au NCs into three distinct states: metallic NCs with a core size larger than 2.3 nm (> Au 333 ), transition NCs with a diameter of 2.3-1.7 nm (Au 333 ∼ Au 144 ), and nonmetallic NCs with a core size smaller than 1.7 nm (< Au 144 ). [40,52,55] They found that the Au NCs in the transition regime exhibited excellent catalytic activity in both CO oxidation and electrocatalytic alcohol oxidation compared with metallic and nonmetallic NCs.…”
Section:  Size Effectmentioning
confidence: 99%
“…Therefore, in this section, we describe the use of Au n (SR) m NCs to enhance the functionality of various electrode reactions. [90,[258][259][260][261][262][263] These reactions comprise the water-splitting reactions (hydrogen evolution reaction [HER] and oxygen evolution reaction [OER]; Section 6.1), cathode reactions in fuel cells (oxygen reduction reaction [ORR]; Section 6.2), and the CO 2 reduction reaction (CO 2 RR; Section 6.3).…”
Section: Electrocatalysismentioning
confidence: 99%